Relationship between client satisfactions, service quality and client perception towards the effectiveness of client consultation services / Romzan Bujang - Bujang, Romzan (2015)
The problem that causes the level of bankrupt’s satisfaction and perception through the interview session or the so-called consultation session has become a major issue in delivering a service quality provides by MdI as a government agency. Misinterpretation, communication barriers, the attitude of the officer, and the way service was the part of the reason that cause the effective internal consultation is an essential prerequisite for effective consultation service.